High-precision Nuclear Chronometer for the Cosmos - Wu, X. H.; Zhao, P. W.; Zhang, S. Q.; Meng, J. (The Astrophysical journal, 2022)
Nuclear chronometers, which predict the ages of the oldest stars by comparing the present and initial abundances of long-lived radioactive nuclides, provide an independent dating technique for the cosmos. The idea of synchronizing Th/X, U/X, and Th/U chronometers can impose stringent constraints on the astrophysical conditions in the r -process simulations, giving rise to the Th-U-X chronometer. It is found that the astrophysical uncertainties of nuclear cosmochronology are significantly reduced from more than ±2 billion years to about 0.3 billion years. The Th-U-X chronometer is then applied to estimate the ages of the six metal-poor stars with observed uranium abundances, and the predicted ages are compatible with the cosmic age of 13.8 billion years predicted from the cosmic microwave background radiation but contradict the cosmic age of 11.4 billion years from the gravitational lens measurement.